Hardware simulation of cooperative adaptive cruise control based on fuzzy logic - Edi Rakhman; Noor Cholis Basjaruddin; Didin Saefudin; Rizky Hartono; Rachmad Imbang Tritjahjono (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2026)
Cooperative adaptive cruise control (CACC) is a system designed to maintain a vehicle’s distance according to the driver’s preset value. It is an advancement of adaptive cruise control (ACC), which suffers from response delays when reacting to changes in the leading vehicle’s speed. CACC addresses this limitation by reducing response delay through the use of speed data from the preceding vehicle, obtained via wireless communication. In this research, the CACC system was simulated using a 1:10 scale remote-control (RC) car equipped with ultrasonic sensors and radio frequency (RF) communication. Speed control was implemented using a fuzzy logic controller with the Mamdani inference method, while an active steering assistance system was added to maintain lane alignment. Hardware simulation results demonstrate that the CACC system functions effectively and significantly improves the response time of the following vehicle when the leading vehicle changes speed. Experimental results show that the CACC maintained the desired following distance in 10 seconds, compared to 15 seconds for the ACC system.